Cultural antecedents to the normative, affective, and cognitive effects of domestic versus foreign purchase behavior - Conner, Suzanne L.; Reardon, James; Miller, Chip; Salciuviene, Laura; Auruskeviciene, Vilte (Journal of Business Economics and Management, 2017)
The paper aims to investigate simultaneous and independent effects of cognitive, affective, and normative (CAN) decision mechanisms and cultural elements on consumer purchase behavior of foreign and domestic products. The study uses a survey to collect data from 5 086 respondents across 19 nations. The findings suggest that CAN factors independently affect purchase decisions for domestic, but not always foreign goods. Collectivism and uncertainty avoidance directly and differentially affect the CAN mechanisms. By explaining the effects of CAN and cultural elements on foreign and domestic purchase behaviour and offering product positioning strategies to internationally operating business managers the study provides important research and practical implications. The originality and value of this research lies in the theoretically proposed and empirically tested model, which incorporates consumer ethnocentrism, quality importance, national identification, cultural antecedents (collectivism and uncertainty avoidance) and domestic/ foreign product purchase behaviour.